Helpful or harmful? A scoping review of perceptions and outcomes of autism diagnostic disclosure to others. (September 2020) - Thompson-Hodgetts, Sandra; Labonte, Chantal; Mazumder, Rinita; Phelan, Shanon
Highlights: Deciding to disclose a diagnosis of autism to others can be a major decision. People with autism and others differ in perspectives of disclosure outcomes. Others perceive primarily positive outcomes of disclosure. People with autism often experience negative outcomes and stigma from disclosure. Critical reflexivity about assumptions related to autism and disclosure is necessary. Abstract: Background: Deciding to disclose a diagnosis of autism to others can be a major decision for people with autism and their families. This scoping review summarizes existing literature related to perceptions and outcomes of disclosing an autism diagnosis to others (e.g., teachers, peers, employers). Methods: We conducted a scoping review of scientific literature using Arksey and O'Malley's (2005) methodological framework. Relevant English language databases and reference lists were searched using terms related to autism, disclosure, and perspective (e.g., attitude, accept*). Studies that focused on disclosure to the person with autism and/or their parents were excluded. Results: A total of 37 articles met inclusion criteria, including 14 that presented the perspective of people with ASD, four that presented the perspective of parents/family members, and 20 that presented the perspective of others. Our findings highlight disconnect in perspectives between others (primarily evaluated through vignettes) and persons with autism (primarily elicited through qualitative interviews). Others perceive that disclosure has positive effects on social acceptance and perceptions of disability for people with autism, especially when explanatory information about autism was provided with the autism label. Adolescents and adults with autism indicated reluctance to disclose their diagnosis due to perceived negative outcomes and stigma. Existing research also reflected an assumption that diagnosis should be disclosed. Conclusions: Professionals and the general public should be aware of their assumptions related to autism and disclosure. More research on the processes and outcomes of diagnostic disclosure in autism, across the lifespan and in real life social contexts, is warranted.